Concentration and reserves of nitrogen in soils and plant matter in blocks of grass ecosystems of the North‐Western Precaspian region, Russia - G. N. Gasanov; T. A. Asvarova; K. M. Gadzhiev; R. Z. Usmanov; M. A. Arslanov; M. R. Musaev; R. R. Bashirov; K. B. Gimbatova; A. S. Abdulaeva (Юг России: экология, развитие, 2023)
Aim. Determination of phytocenosis productivity, nitrogen concentration and reserves in blocks of plant associations and by soil types in the North‐Western Precaspian region of Russia. Methods. Comprehensive research on the accumulation of organic matter and nitrogen in five blocks of plant matter, six plant associations and three types of soil by season using well‐known methods of accounting and analysis of soils and plants. Results. The regularities of phytomass formation, changes in nitrogen concentration and reserves in the main soil types and six plant associations for the 2011–2018 seasons were revealed. Conclusions. Ephemeroid‐wormwood‐cereal, ephemeroid‐wormwood, cereal‐wormwood, forb‐campfire and mixed‐grass‐campfire plant communities formed on light chestnut soil are the most productive, with a total productivity of 24.34 t/ha. The maximum nitrogen concentration was observed in the cereal‐wormwood, wormwood‐saltwort, forb‐saltwort and cereal‐saltwort associations – 1.9, 1.97, 2.2, and 2.57%, respectively, which is due to the predominance of Artemisia taurica Willd., Artemisia lercheana Web.ex Stechm. and Salsola iberica Sennen&Pau. In associations where there are representatives of the Poaceae, Brassicaceae and Caryophyllaceae, nitrogen decreases to 1.72–1.74%. Its value was higher on light‐chestnut soil, being 1.82% of absolutely dry mass, while on meadow‐chestnut soil it decreased to 1.75 and on saline soil is typically 1.38%. In the root mass of plant associations, its indicators were 3.2 times less than in the above ground mass. Nitrogen reserves by blocks of plant matter formed the following decreasing series: roots ≥ green mass ≥ rags ≥ felt. In the input part of the balance in plant associations, 171.6 nitrogen accumulates on light‐chestnut soil, 63.1 on meadow‐chestnut soil, 49.1 kg/ha on automorphic typical saline soil, and 171.9; 64.3 and  58.1 kg/ha in the expenditure part, respectively. the balance of nitrogen in the first type of soil is formed with a minimum deficit of 0.6 kg/ha, 1.2 and 9 kg/ha, respectively.